IMF Staff papers : Volume 6 No. 2. (IMF Staff Papers; IMF Staff Papers, 1958)
This paper examines the effect transactions with the IMF have on the monetary situation within a country when the foreign exchange purchased from the IMF is used to meet a balance of payments deficit. In some countries, the national currency counterpart is kept on deposit to the credit of the IMF at the central bank. In other countries, the government substitutes a noninterest-bearing note for the national currency counterpart of a transaction with the IMF. It is with the effects of the latter practice that this paper is primarily concerned. The effect of a balance of payments deficit on the money supply will be offset if credit is expanded to finance a government deficit, investment by business, or spending by consumers. The ultimate effect on the money supply will depend upon how the government deals with the national currency turned over to it by the Exchange Equalization Account. Considerable caution is required in concluding that a balance of payments deficit is likely to be moderate and temporary.